Place et rôle des jeux numériques dans le développement des activités narratives dans une classe de FLE - Kotuła, Krzysztof (Studia Romanica Posnaniensia, 2019)
The aim of the present article is to focus on the potential of video games as a tool enabling the language teacher to transform the learning experience in the FL classroom. Apart from presenting various theoretical aspects of integrating computer-enhanced ludic techniques into language teaching, learner discourse excerpts will be analysed in order to determine the extent to which video games implementation can enhance classroom interaction. Our main aim will be to list various contexts in which narrative activities can manifest themselves during French as a foreign language lessons. As we will see, learners can be encouraged to create stories not only in reaction to cinematic sequences but also when attempting to reconstruct events which occurred earlier in the game or while recalling events from an earlier gaming session.